Identification of an histone H3 acetylated/K4-methylated-bound intragenic enhancer regulatory for urokinase receptor expression - Wang, H.; Yan, C.; Asangani, Irfan A.; Allgayer, Heike; Boyd, D. D. (Oncogene, 2007)
The transcriptionally regulated urokinase-type plasminogen activator receptor (u-PAR) contributes to cancer progression. Although previous studies have identified multiple 5′ regulatory elements, these cis motifs cannot fully account for u-PAR expression prompting a search for hitherto uncharacterized regulatory elements. DNase I hypersensitivity and chromatin immunoprecipitation assays using u-PAR-expressing colon cancer cells indicated a hypersensitive region (+665/+2068) in intron 1 enriched with acetylated histone 3 (H3) and H3 methylated at lysine 4, markers of regulatory regions. The +665/+2068 region increased transcription from a u-PAR-promoter in an orientation- and distance-independent manner fulfilling the criteria of an enhancer. Optimal stimulation of the u-PAR promoter by phorbol ester required this enhancer. Systematic truncations combined with DNase I footprinting revealed two protected regions (+1060/+1099 and +1123/+1134) with deletion of the latter practically abolishing enhancer activity. The +1123/+1134 region harbored non-consensus activator protein-1 and Ets1 binding sites bound with c-Jun (and/or the related JunD/JunB) and c-Fos (and/or the related FosB/Fra-1/Fra-2) as revealed with chromatin immunoprecipitation. Further, nuclear extract from resected colon cancers showed elevated protein binding to a +1123/+1134-spanning probe coordinate with elevated u-PAR protein. Thus, we have defined a novel intragenic enhancer in the u-PAR gene required for constitutive and inducible expression.
Published online 25 September 2006
Gesehen am 02.05.2022